Characterization of Phenotypic and Genotypic Diversity of Stenotrophomonas maltophilia Strains Isolated From Selected Hospitals in Iran - Bostanghadiri, Narjess; Ghalavand, Zohreh; Fallah, Fatemeh; Yadegar, Abbas; Ardebili, Abdollah; Tarashi, Samira; Pournajaf, Abazar; Mardaneh, Jalal; Shams, Saeed; Hashemi, Ali (Frontiers in Microbiology, 2019)
The purpose of this study was to determine the phenotypic and genotypic characterization of S. maltophilia isolates recovered from patients referred to several hospitals. A total of 164 clinical isolates of S. maltophilia were collected from hospitals in various regions in Iran between 2016 and 2017. Antibiotic susceptibility testing was performed by disc diffusion method and E-test assay according to the Clinical and Laboratory Standards Institute(CLSI) guideline. The ability of biofilm formation was assessed with crystal violet staining and then, biofilm-associated genes were investigated by PCR-sequencing method. The presence of L1 (a metallo-β-lactamase), L2(a clavulanic acid-sensitive cephalosporinase), sul1 and sul2 (resistance to Trimethoprim/Sulfamethoxazole),Smqnr (intrinsic resistance to quinolones) and dfrA genes (dihydrofolate reductase enzyme that contributes to trimethoprim resistance) was also examined by PCR-sequencing. Relative gene expression of smeDEF efflux pump was assessed by real-time PCR. Genotyping was performed using the multi-locus sequencing typing (MLST) and repetitive extragenic palindromic-PCR (Rep-PCR).Isolates were resistant to imipenem (100%),meropenem (96 %),doripenem (96%),and ceftazidime (36.58%). Notably, 5 (3.04%) isolates showed resistant to trimethoprim-sulfamethoxazole (TMP-SMX), an alarming trend of decreased susceptibility to TMP-SMX in Iran. Minocycline and levofloxacin exhibited the highest susceptibility of 91.46% and 99.39%, respectively. Using the crystal violet staining, 157(95.73%) isolates had biofilm phenotype: 49 (29.87%), 63 (38.41%), and 45 (27.43%) isolates were categorized as strong-, moderate- and weak-biofilm producer while 7 isolates (4.26%) were identified a non-biofilm producer. Biofilm genes had an overall prevalence of 145(88.41%), 137(83.53%),and 164(100%) of rmlA, rpfF and spgM, respectively. L1, L2, Smqnr, sul1, and sul2 resistance genes were detected in 145(88.41%), 156(96.12%), 103(62.80%), 89 (54.26%), 92 (56.09%) isolates, respectively. None of the S. maltophilia isolates were positive for dfrA12, dfrA17, and dfrA27 genes. Gene expression analysis showed that smeD efflux system was overexpressed in 2 out of the 5 clinical isolates (40%) that showed resistance to TMP-SMX. Most of the isolates were genetically unrelated. Two new sequence types(ST139 and ST259) were determined. Our results showed that TMP-SMX was still an effective antibiotic against S. maltophilia. The findings of the current study revealed an increasing prevalence of antibiotic resistance and biofilm genes in clinical S. maltophilia isolates in Iran.